Princely Bahawalpur: On the Brink of Muslim Rule in India - Dr. Zahra Akram Hashmi; Dr. Samia Khalid (Al-Qamar, 2020)
Bahawalpur State, a premier Muslim state of northern India, preponderate a rich historical legacy. Bahawalpur evolved as an Islamic entity and assimilated with the Mughal rule of India. This paper evaluates the state during both the traditional Mughal polity and the rule of East India Company. The paper concentrates two areas; first it investigates the lesser-known aspects of the history of warrior band of daudputras that how they apprehended in this realm and consolidated a scattered area. The other is to search the advantages of entering the political relationship with the British and to review the extent of their cooperation with them when their local patterns were replaced according to the imperial interests.